2016
DOI: 10.1515/cipms-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mutation and promoter methylation of TP53 gene in tumors of the head and neck

Abstract: According to current World Health Organization data, worldwide, cancer is second to cardiovascular diseases as the leading cause of death. The p53 protein is a translation product of the TP53 gene, and it has many functions in cells. Indeed, for this, it is commonly called the “guardian of the genome”. The aim of this study was to evaluate the prevalence of mutation and methylation in the promoter of the TP53 gene in cells affected with squamous cell carcinoma of the head and neck. The research material consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Although positive prognostic impact of p53 mutation is controversial, some researchers have supported this relationship (28) while others were dissenters of this possibility (29) . The significant association between the p53 methylation and the ATC status that has been found in the current study, is supported by other studies, in a study conducted by Adrian et al, they analyzed the changes in the methylation profile of the CpG dinucleotides within the TP53 gene promoter in -139 and -132, they revealed the presence of methylated cytosines in these places and the majority of the tested DNA samples in their study showed the presence of methylation of both alleles (complete methylation), while the methylation of a single allele (partial methylation) was seen in lower rate among the studied patients (30) .…”
Section: Discussion P53 Methylationmentioning
confidence: 94%
“…Although positive prognostic impact of p53 mutation is controversial, some researchers have supported this relationship (28) while others were dissenters of this possibility (29) . The significant association between the p53 methylation and the ATC status that has been found in the current study, is supported by other studies, in a study conducted by Adrian et al, they analyzed the changes in the methylation profile of the CpG dinucleotides within the TP53 gene promoter in -139 and -132, they revealed the presence of methylated cytosines in these places and the majority of the tested DNA samples in their study showed the presence of methylation of both alleles (complete methylation), while the methylation of a single allele (partial methylation) was seen in lower rate among the studied patients (30) .…”
Section: Discussion P53 Methylationmentioning
confidence: 94%
“…At first, DNA bisulfite conversion is done with the aid of the EpiTect fast bisulfite conversion kit from Qiagen (Germany) and all steps were done according to the manufacturer's instructions. Then the converted DNA samples were amplified using M-P53-F 5ʹ-TTCGGTAGGCGGATTATTTG-3ʹ and M-P53-R 5ʹ-AAATATCCCCGAAACCCAAC-3ʹ primers for the methylated TP53 gene and U-P53-F 5ʹ-TTGGTAGGTGGATTATTTGTTT-3ʹ and U-P53-R 5ʹ-CCAATCCAAAAAAACATATCAC-3ʹ primers for the un-methylated TP53 gene 21. Initially a master mix was prepared using 2X Hot Start Master Mix from GeNet Bio (South Korea) and then amplification was performed using a PCR thermal cycler (2720) from Applied Biosystems, Hitachi (Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Inactivation of the 14-3-3 sigma gene is associated with 5' CpG island hypermethylation in human cancers [93,94] . Promoter hypermethylation of p53 genes is detected in many cancers [95][96][97] .…”
Section: Methylationmentioning
confidence: 99%